Preoperative evaluation of bone quality for dental implantation using an ultrasound axial transmission device in an ex vivo model. Issue 3 (9th June 2017) - Okada, Shinsuke; Kawano, Akira; Oue, Hiroshi; Takeda, Yosuke; Yokoi, Miyuki; Koretake, Katsunori; Tsuga, Kazuhiro
Abstract: This study investigated the clinical utility of an ultrasound axial transmission device in preoperative evaluation of bone quality for dental implantation, by clarifying the relationship between cortical bone speed of sound (cSOS), insertion torque values (ITV), and implant stability quotient (ISQ) in porcine femur bone. Eleven fresh porcine femurs, without soft tissue, were prepared. The cSOS of these bones were measured using the axial transmission device. Bone mineral density (BMD) and porosity (Po) were measured in cortical bone samples obtained from the region of ultrasound measurements by X‐ray microcomputed tomography. Thirty‐three implants were inserted into these samples (three implants per bone sample), and ITV and ISQ were measured for all implants. Then, cortical bone thickness (CbTh) of the area for implantation was measured for all implants using a micrometer. The mean cSOS was 3962 m/s; mean BMD and Po were 0.822 g/cm2 and 0.185%, respectively. cSOS and BMD values were positively correlated, and cSOS values and Po values were negatively correlated. Mean ITV, ISQ, and CbTh were 37.95 Ncm, 71.172, and 2.869 mm, respectively. There was a positive correlation between cSOS values and ISQ values. The cSOS of each bone did not correlate with ITV for all of the bone samples. However, when the CbTh ranges from 3.0 to 3.5 mm, ITV are correlated with cSOS. These findings suggest that cSOS, which reflects the cortical bone quality, may be clinical utility as a preoperative diagnosis of the implant.